2009
DOI: 10.1002/clc.20458
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Sedentary Lifestyle in the Morbidly Obese

Abstract: Background: Sedentary lifestyles and poor physical fitness are major contributors to the current obesity and cardiovascular disease pandemic. Hypothesis: Daily physical activity and cardiorespiratory fitness are correlated in morbidly obese individuals in their free-living environment. Methods: Ten morbidly obese participants continuously wore an activity sensor that measured caloric expenditure, minute-by-minute physical activity, and steps/day over a 72-h period. Following collection of the device data, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
(21 reference statements)
2
40
0
Order By: Relevance
“…Previous studies have shown that obesity is associated with a high expenditure of energy needed to move a greater corporal mass [13,14]. This high expenditure of energy reduces exercise capacity and shortens the duration of the test [5].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have shown that obesity is associated with a high expenditure of energy needed to move a greater corporal mass [13,14]. This high expenditure of energy reduces exercise capacity and shortens the duration of the test [5].…”
Section: Discussionmentioning
confidence: 98%
“…However, it remains to be determined whether poor physical fitness and sedentary lifestyle is an important characteristic of these patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,186,187 According to 1 report, exercisers lost an average of 6.1 kg more than inactive patients, suffered less depression and anxiety, and had higher scores in general health. 187 Because severely obese individuals are often completely sedentary, 188 they should be strongly encouraged to engage in regular walking so that they can move out of the least fit, least active, "high-risk" cohort. Surgically induced weight loss can also increase peak heart rate, respiratory exchange ratio, and relative oxygen consumption (mL ⅐ kg Ϫ1 ⅐ min Ϫ1 ), augmenting the exercise capacity.…”
Section: Physical Activitymentioning
confidence: 99%
“…At this point, the attention should be brought to the fact that spontaneous locomotion and physical activity levels are, like meal-to-meal eating, under nonhomeostatic control although their interaction brings about the stability of adult body weight [284] . Cross-sectional human data show that total non-basal energy expenditure normalized for body mass is inversely related to body fat [285,286] , and that morbidly obese individuals are almost completely inactive [287] . On the other extreme, underweight subjects with anorexia nervosa are known for compulsive running, "drive for activity", and "restlessness" [288,289] .…”
Section: Body Mass Lossmentioning
confidence: 99%